2015
DOI: 10.5051/jpis.2015.45.3.101
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperglycemia increases the expression levels of sclerostin in a reactive oxygen species- and tumor necrosis factor-alpha-dependent manner

Abstract: PurposeSclerostin, an inhibitor of Wnt/β-catenin signaling, exerts negative effects on bone formation and contributes to periodontitis-induced alveolar bone loss. Recent studies have demonstrated that serum sclerostin levels are increased in diabetic patients and that sclerostin expression in alveolar bone is enhanced in a diabetic periodontitis model. However, the molecular mechanism of how sclerostin expression is enhanced in diabetic patients remains elusive. Therefore, in this study, the effect of hypergly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 34 publications
(39 reference statements)
2
31
1
2
Order By: Relevance
“…It has been suggested that high glucose concentrations stimulate sclerostin secretion in osteoblastic and osteocytic cell lines. Consistent with previous data, our results show increased sclerostin production in UMR-106 cells with increasing glucose concentrations, implying a stimulatory effect of hyperglycaemia on sclerostin production [35, 36]. However, we could not detect sclerostin expression in the osteocytic cell line IDG-SW3 at any stage of differentiation, suggesting that IDG-SW3 cells might not be suitable for the study of sclerostin expression.…”
Section: Discussionsupporting
confidence: 85%
“…It has been suggested that high glucose concentrations stimulate sclerostin secretion in osteoblastic and osteocytic cell lines. Consistent with previous data, our results show increased sclerostin production in UMR-106 cells with increasing glucose concentrations, implying a stimulatory effect of hyperglycaemia on sclerostin production [35, 36]. However, we could not detect sclerostin expression in the osteocytic cell line IDG-SW3 at any stage of differentiation, suggesting that IDG-SW3 cells might not be suitable for the study of sclerostin expression.…”
Section: Discussionsupporting
confidence: 85%
“…In cytokine imbalance caused by hyperglycemia, it has been extensively reported that inflammatory cytokines, such as TNF- 10) , IL-1 11) , and IL-6 11) , increase. These inflammatory cytokines both directly and indirectly promote differentiation and activation of osteoclasts 13) .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we have reported that expression of the angiogeneic factor VEGF in the periodontium is increased in rats with diabetes mellitus when compared to that in healthy rats 22) . Hyperglycemia-induced increases in levels of inflammatory cytokines, such as TNF- 10) , IL-1 11) and IL-6 11) , cause progression of periodontitis in diabetes mellitus. However, how VEGF, a cytokine expressed and present in the periodontium under hyperglycemic conditions, affects bone resorption caused by periodontitis is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations